Potensi Seresah Ketiak Pelepah Kelapa Sawit untuk Pertumbuhan Pueraria Javanica di Pembibitan - . Yuliyanto (Politeknik Kelapa Sawit Citra Widya Edukasi, 2020)
The problem that arises in plant cultivation is the limitation of top soil as a planting medium, one of the substitutes for top soil is litter. Litter comes from weathering of male flowers, female flowers and sheath weathering which have decayed and become organic matter. The aim of the study was to determine the effect of armpit litter growing media on oil palm trunks on the growth of Pueraria javanica, determine good media, and determine the nutrient content of armpit litter on oil palm trunks. The research was carried out in the experimental garden 1 Politeknik Kelapa Sawit Citra Widya Edukasi from February to April 2018. This study used a Complete Randomized Block Design (RAKL), with treatment A1: 100% Top Soil, A2: Litter 100%, A3: Subsoil 80% + litter 20%, A4: Subsoil 60% + litter 40%, A5: Subsoil 40% + litter 60%. One treatment had three replications, and each replication consisted of three samples. If there is a real effect, it is tested further with the DMRT test (Duncan Multi Range Test) 5%. The parameters of observation were plant height, stem diameter, number of leaves, leaf area, wet weight and dry weight. Based on the results of the study, giving litter of oil palm midrib armpit significantly affected the growth of Pueraria javanica, such as plant height from age 1 and 2 BST (Month after Planting) and stem diameter, number of leaves, leaf area at 2 BST (Month after Planting), A5 treatment has a good effect on plant height and leaf area, while A4 treatment is the best medium for stem diameter and number of leaves. Litter content is N 2.09%, P 0.08%, and K 0.179%.